CHARTER THE TOBACCO INDUSTRY LABOR/MANAGEMENT COMMITTEE (Tufts Archival Research Center, 2007)
Charter of the Tobacco Industry Labor Management Committee (LMC). Provides mission statement and organizational structure of the LMC. Defines membership, meeting, and governing procedure.